Transforming music learning: Keroncong guitar VSTi prototype as a catalyst for educational innovation - Kusuma, Adel Sulaiman; Sukmayadi, Yudi; Riyadi, Lanang (Universitas Negeri Yogyakarta, 2024)
The rapid development of technology in music education requires music educators to be creative and critical in developing technology-based learning tools. This ensures that learning aligns with current trends and is implemented more effectively. In addition to enhancing learning, technology also addresses challenges faced by music composers. This study focuses on creating a Virtual Studio Technology Instrument (VSTi) for the keroncong guitar as a teaching aid. In keroncong music, the guitar plays a key role in improvising chord progressions, demanding specialized skills from musicians and composers. Using a practice-oriented approach, this study covers the pre-production, production, and post-production stages of developing a VSTi for the Keroncong guitar. The results show that the VSTi operates effectively in a Digital Audio Workstation (DAW), serving as a valuable learning tool and reference for keroncong guitar patterns. The assessment demonstrated significant improvements in sound quality and user satisfaction, with 90% of users approving. Integration with other instruments showed a 25% average improvement, while flexibility and ease of improvisation received positive feedback from 80% and 75% of users. To conclude, the prototype of the Keroncong Guitar VSTi can catalyze educational innovation.